Inorganic phosphate‐induced cytotoxicity. Issue 1 (22nd October 2021) - Alexander, Rachel; Debiec, Nicholas; Razzaque, Mohammad S.; He, Ping
Abstract: Phosphate, an essential nutrient, is available in organic and inorganic forms. The balance of phosphate is central for cellular homeostasis through the genomic roles of DNA and RNA synthesis and cell signaling processes. Therefore, an imbalance of this nutrient, manifested, either as a deficiency or excess in phosphate levels, can result in pathology, ranging from cytotoxicity to musculoskeletal defects. Inorganic phosphate (Pi) overdosing can result in a wide spectrum of cytotoxicity processes, as noted in both animal models and human studies. These include rewired cell signaling pathways, impaired bone mineralization, infertility, premature aging, vascular calcification, and renal dysfunction. This article briefly reviews the regulation of phosphate homeostasis and elaborates on cytotoxic effects of excessive Pi, as documented in cell‐based models.